An injectable calcium sulfate-monetite biphasic cement for the treatment of critical-sized calvarial defects - Jianzhong Bai; Dachuan Liu; Luguang Ding; Guoping Liu; Jiaying Li; Huan Wang; Li Dong; Chen Cui; Youzhi Hong; Shuangjian He; Song Chen; Hongtao Zhang (Journal of Materials Science: Materials in Medicine)
Abstract The critical bone defect is a common clinical challenge worldwide, characterized by long recovery times, a substantial risk of infection, and high disability rates. There remains a significant demand for synthetic bone-repairing materials to address this issue. In this study, porous monetite was synthesized through the reaction between monocalcium phosphate monohydrate and β-tricalcium phosphate, using paraffin microspheres as pore-forming agents. An injectable biphasic cement was then developed by blending the monetite granules with hemihydrate calcium sulfate, designed for minimally invasive surgical applications. The cement demonstrated excellent biocompatibility and osteogenic properties in vitro. Furthermore, in vivo studies confirmed the cement’s superior bone repair capabilities, indicating its promising potential for the treatment of critical bone defects. Graphical Abstract A highly porous composite with gradient degradation was developed by mixing porous monetite granules and hemihydrate calcium sulfate, and the composite has the effect of promoting the formation of new bone.